The health of internally displaced people in Syria: are current systems fit for purpose? - Aula Abbara; Diana Rayes; Abdulkarim Ekzayez; Samer Jabbour; Manar Marzouk; Houssam Alnahhas; Sara Basha; Zahed Katurji; Richard Sullivan; Fouad M Fouad (Elsevier, 2022)
Introduction: Syria has the largest number of internally displaced people (IDPs) globally with 6.7 million forced from their homes since the uprising erupted in 2011. Most face multiple intersecting vulnerabilities with adverse health impacts. We explore the key health concerns among IDPs, how the various health systems in Syria have responded to the dynamic health needs of IDPs and what modalities have been used by humanitarian actors to address these needs. Methods: We undertook a scoping review of academic and grey literature for available evidence regarding the health of IDPs in Syria. We then organised an online workshop in November 2021 with around 30 participants who represent local, regional, and international organisations and who have relevant expertise. The discussion focused on how the health systems in Syria's various territories have responded to the health needs of IDPs, what this means to the structure and dynamics of these health systems and their intended outcomes and responsiveness. Findings: These emphasised the weak evidence base around IDP health in Syria, particularly in certain geographical areas. Workshop participants explored the applicability of the term IDP in the Syrian context given the fragmented health system and its impact on IDPs, the importance of considering co-determinants (beyond forced displacement) on the health of IDPs and taking a transectoral, community led approach to identify and respond to needs. Conclusion: This manuscript presents some of the current issues with regards to IDP health in Syria, however, there remain numerous unknowns, both for the health of IDP as well as non-IDP populations. We hope that it will be the foundation for further discussions on practical steps relating to research, analysis and interventions which can support health system responses for IDPs in Syria.